2004
DOI: 10.1111/j.0953-816x.2004.03392.x
|View full text |Cite
|
Sign up to set email alerts
|

An impaired neocortical Ih is associated with enhanced excitability and absence epilepsy

Abstract: Neuronal subthreshold excitability and firing behaviour are markedly influenced by the activation and deactivation of the somato-dendritic hyperpolarization-activated cation current (Ih). Here, we evaluated possible contributions of Ih to hyperexcitability in an animal model of absence seizures (WAG/Rij rats). We investigated pyramidal neurons of the somatosensory neocortex, the site of generation of spike-wave discharges. Ih-mediated functions in neurons from WAG/Rij rats, Wistar rats (sharing the same geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
166
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 167 publications
(184 citation statements)
references
References 54 publications
13
166
1
3
Order By: Relevance
“…Therefore, despite an effect of the treatment on the changes observed in the expression of Na + channels and hyperpolarization-activated cation channels (HCN1), which accompanies the development of SWDs in this strain (see below Section 3.3) (Klein et al, 2004;Strauss et al, 2004), ETH treatment did not seem to influence the function of the circuit in the maintenance of a single seizure once it is started, but only their generation at the focal site(s).…”
Section: Drug Efficacy Against the Development Of Spontaneous Absencementioning
confidence: 87%
See 2 more Smart Citations
“…Therefore, despite an effect of the treatment on the changes observed in the expression of Na + channels and hyperpolarization-activated cation channels (HCN1), which accompanies the development of SWDs in this strain (see below Section 3.3) (Klein et al, 2004;Strauss et al, 2004), ETH treatment did not seem to influence the function of the circuit in the maintenance of a single seizure once it is started, but only their generation at the focal site(s).…”
Section: Drug Efficacy Against the Development Of Spontaneous Absencementioning
confidence: 87%
“…This loss of neocortical HCN1 function may contribute to an increased cortical excitability since there are substantially few HCN1 subunits in the combined complex of the I h channel in the cortical zone containing the focal region in WAG/Rij rats in comparison to non-epileptic rats. Indeed, the density of HCN1 channels in the apical dendrites of the subgranular layers in the cortical onset zone determines the somatodendritic excitability and a decrease of these dendritic HCN1 channels is accompanied by an age-dependent increase of SWDs (Bazyan and van Luijtelaar, 2013;Strauss et al, 2004). Recently, it was demonstrated that HCN1 channels from the thalamus only (not in genomic DNA) of WAG/Rij rats have an N-terminal deletion of 37 amino acids; these channels expressed in Xenopus oocytes indicated a gain-of-function of about 2 fold which was further accompanied by a suppression in HCN2 and HCN4 currents (Wemhoner et al, 2015).…”
Section: Ion Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence in this model of a reduction in HCN1 protein and I h currents in pyramidal neurons in the somatosensory cortex. 164 It has been noted previously that lamotrigine enhances I h , so that it could theoretically reverse this reduction. 170 Lamotrigine is the only classical Na ϩ channel-blocking AED with efficacy in the treatment of absence epilepsy; its unique activity could be due to specific biophysical differences in its action on Na ϩ channels or to additional actions, such as the effect on I h .…”
Section: Molecular Targets For the Treatment Of Absence Seizuresmentioning
confidence: 97%
“…In mice, deletion of the HCN2 subunit produces animals with 5-Hz spike-and-wave discharges and absence-like seizures. 163 The WAG/Rij rat model of ab-sence epilepsy shows a loss of HCN1 function in the cortex 164 (possibly linked to the origin of cortical spikeand-wave discharges) but enhanced HCN1 expression in the thalamus. 165 In addition, changes in I h and in HCN subunit expression have been observed in epileptogenesis.…”
Section: Hcn Channelsmentioning
confidence: 99%